2011
DOI: 10.1007/s00216-011-5532-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of grain development in two spring wheat varieties under drought stress

Abstract: Two spring wheat varieties Ningchun 4 and Chinese Spring with good and poor resistance to abiotic stress, respectively, were used to investigate proteomic changes in the developing grains under drought stress by a comparative proteomics approach. A total of 152 protein spots showed at least twofold differences in abundance on two-dimensional electrophoresis (2-DE) maps, of which 28 and 68 protein spots were identified by MALDI-TOF and MALDI-TOF/TOF mass spectrometry, respectively. Of the 96 identified protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 46 publications
2
88
0
Order By: Relevance
“…A significant decrease in expression of peroxidase was observed under mild osmotic stress conditions. Reduction of peroxidase accumulation by the action of osmotic stress was observed in other studies (Jiang and Deyholos 2006;Ma et al 2009;Ge et al 2012). Decrease in the abundance of this enzyme in the tissues could reduce the adaptability of the plants to stress as evidenced, for example, in the study of Arabidopsis mutants, deprived of the ability to synthesize ascorbate peroxidase (Koussevitzky et al 2008).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A significant decrease in expression of peroxidase was observed under mild osmotic stress conditions. Reduction of peroxidase accumulation by the action of osmotic stress was observed in other studies (Jiang and Deyholos 2006;Ma et al 2009;Ge et al 2012). Decrease in the abundance of this enzyme in the tissues could reduce the adaptability of the plants to stress as evidenced, for example, in the study of Arabidopsis mutants, deprived of the ability to synthesize ascorbate peroxidase (Koussevitzky et al 2008).…”
Section: Discussionmentioning
confidence: 64%
“…This enzyme is involved in synthesis of a-glucan, found in the plant's primary reserve material-starch (Hochstenbach et al 1998;Kok-Jacon et al 2003). It was demonstrated that osmotic stress causes changes in the biosynthesis of starch (Ge et al 2012). A reduced demand for carbohydrates in cells may be due to the inhibition of triticale growth under osmotic stress (Brosowska-Arendt and Weidner 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MS-based proteomics has the potential to identify novel proteins that are related to the action mechanisms of natural products (Barnett et al, 2012;Schrattenholz et al, 2010;Zhang et al, 2013). Various types of biological networks are being constructed, including protein-protein interaction networks, and protein regulatory networks, to help drug discovery (Abu-Asab et al, 2011;Ge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2-DE was performed according to Ge et al (2011), and 600 ÎŒg of proteins was loaded into analytical and preparative gels (pH 3-10, 18 cm, GE Healthcare). The 2-DE experiments of each sample were repeated 2-3 times.…”
Section: -De and Image Analysismentioning
confidence: 99%